Persuasive Language in Pauline Hanson's Speech - Nurjihan Nabilah; Nur Israfyan Sofian (ELITE: Journal of English Language and Literature, 2024)
The objective of this research is to describe and find out the kinds of linguistic tools for influence and persuasion used in Pauline Hanson's speech using McPheat’s theory. This research used a qualitative descriptive method where the data refers to the speech, and the source of data is written words and utterances in speech. The data were collected by watching the video and the transcript of the speech and selecting the related tools for persuasion. The data were analyzed by presenting, describing, interpreting, and concluding the data. The results show that her speech to the Senate was a highly persuasive speech that had a significant impact on Australian politics. Hanson used a variety of linguistic tools to persuade her audience, especially using someone's name lost performative, reframing, cause-effect relationship, tag questions, presupposition, and embedded commands. Her speech was particularly persuasive because it appealed to a sense of grievance and frustration that many Australians were feeling at the time. Many Australians were concerned about the country's high immigration rate, the loss of jobs to overseas workers, the increasing diversity of Australian society, and also the sensitive issue of Islam and its teachings. Her speech gave voice to these concerns and offered a simple solution: reduce immigration and Islamic teachings and return to a more traditional Australian identity.